Prevention of ACL injuries with proprioception training
Proprioception training can be used by youth soccer coaches and college soccer coaches to reduce the incidence of ACL injuries in soccer players. The training needed can be provided as a small part of daily soccer fitness activities with very little or no training equipment. When equipment is used at home or at the field, only modestly priced equipment such as balance pads, wobble boards, or fitness bands will be needed.